Kemampuan Berpikir Reflektif Matematis Siswa Menyelesaikan Soal Bertipe HOTS Ditinjau dari Gaya Belajar - Aditya Laili, Luthfiana; Swastika , Annisa; Noor Kholid, Muhammad (Universitas Islam Ahmad Dahlan (UIAD), 2024)
One of the higher order thinking skills is reflective thinking which students can do when they feel confused in dealing with a math problem. One of them is when dealing with HOTS type questions. Efforts to maximize the ability to think reflectively by knowing the type of learning style of each student. This form of qualitative descriptive research was conducted to determine the ability to think reflectively mathematically in solving HOTS questions in students with visual learning styles, auditory learning styles, and kinesthetic learning styles. The subjects of this study were students of class X SMA with a purposive sampling technique of quadratic equation material. The research instrument was in the form of HOTS test questions by paying attention to indicators of reflective thinking and interviews. The results of this study are that students with a visual learning style can meet the indicators of reacting, comparing, pondering. Students with an auditory learning style can meet the indicators of reacting and comparing. Meanwhile, students with kinesthetic learning styles can fulfill the reacting indicators.